The medical lives of history's famous people - Maloney, William James (Bentham Science Publishers, Inc., 2014)
The Medical Lives of History`s Famous People highlights the effects of various diseases on the public lives of famous individuals in history. The contents of this eBook include chapters on the historical facts concerning Babe Ruth`s heroic battle with nasopharyngeal carcinoma, the oral cancer affecting Sigmund Freud, Celiac disease (the cause of president John F. Kennedy`s lifelong medical travails), porphyria (the condition afflicting King George), Hemophilia (the 'Royal disease') and much more. The Medical Lives of History`s Famous People is an interesting and valuable resource for general readers and researchers, alike, seeking historical information about several medical ailments.